PENGARUH LATIHAN QUICK LEAP TERHADAP POWER OTOT TUNGKAI PEMAIN BOLA VOLI CLUB PKDP KOTA PEKANBARU - amri, Mhd khairul; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is "Muscle strength of the PKDP Club volleyball players in Pekanbaru City?", So that players in the future can perform and play much better, and most importantly, after having received a training in limb muscle power, the player advance increases the opponent's game and achieve maximum performance in the future. The form of this research is (Experiment), with a population of club volleyball players in the city of Pekanbaru. The data in this research are all populations of 8 people. The instrument in this research is Vertical Power Jump, with which the endurance is measured. The data were then processed with statistics to test the normality using the liliefors test at a significant level of 0.05 α. The proposed hypothesis is the influence of the Quick Leap (Exerc Leap) exercise on the Force of Leg Muscles, which produces a Tcount of 12.64 and T-Table 1.895 based on the analysis of the t-test. Means Thitung> Ttable On the basis of statistical data analysis there is an average pree test of 18.45 and the average after the test is 20.22, after which the data is distributed normally. For example, there is the Quick Leap Exercise Effect (Quick Leap) on the Muscle Power or Volleyball Players in the PKDP Club in Pekanbaru City.Keywords: Exercise Quick Leap (Quick Leap), Put Muscle Power